Computational analysis of the deformation behavior of 4D-printed liquid crystal elastomers under change of temperature - Schek, Lucca; Vilchevskaya, Elena Nikitichna; Müller, Wolfgang Helmut (Національний технічний університет "Харківський політехнічний інститут", 2025)
This paper focuses on an FE simulation of Liquid Crystal Elastomers (LCE). For this purpose, a new method is proposed based on the combination of nonlinear deformation analysis based on a St. Venant – Kirchhoff law, i.e., a physically linear but geometrically nonlinear stress-strain relationship. The deformation gradient is decomposed multiplicatively into elastic, (classical) thermal, and phase transformation parts. For the transformation part a novel representation is chosen based on an orientation parameter within a distribution function for the mesogens. This parameter can be linked to temperature. The stiffness tensor in the St. Venant – Kirchhoff law as well as the tensor of thermal expansion (for the thermal part of the deformation gradient) are obtained from Mori-Tanaka homogenization schemes. It is shown that classical thermal expansion with positive expansion coefficients and realistic values does not contribute much to the total large deformations. The mayor contribution comes from phase transformation. It is, therefore, misleading to model the deformation of LCEs during temperature change by classical thermal expansion, although exactly this is done in the literature by a trick–namely, using negative anisotropic thermal expansion coefficients. Ця стаття зосереджена на моделюванні методом скінченних елементів рідкокристалічних еластомерів (РКЕ). Для цього запропоновано но- вий метод, заснований на комбінації нелінійного аналізу деформації на основі закону Сен-Венана – Кірхгофа, тобто фізично лінійної, але геометрично нелінійної залежності напруження-деформації. Градієнт деформації мультиплікативно розкладається на пружну, теплову та фазово-перетворювальну частини. Для перетворювальної частини вибрано нове представлення на основі параметра орієнтації в межах функції розподілу мезогенів. Цей параметр може бути пов’язаний з температурою. Тензор жорсткості в законі Сен-Венана – Кірхгофа, а також тензор теплового розширення (для теплової частини градієнта деформації) отримані зі схем гомогенізації Морі-Танаки. Показано, що класичне теплове розширення з позитивними коефіцієнтами розширення та реалістичними значеннями не робить значного внеску в загальну величину великих деформацій. Тому моделювання деформації РКЕ під час зміни температури за допомогою класичного теплового розширення є помилкою, хоча саме це робиться в літературі за допомогою хитрощів, а саме, використовуючи негативні анізотропні коефіцієнти теплового розширення.
Обчислювальний аналіз деформаційної поведінки рідкокристалічних еластомерів, надрукованих за допомогою 4D-друку, при зміні температури
Keywords: 4D printing; liquid crystal elastomer; FE simulation; Mori-Tanaka scheme; distribution function; shape function; 4D-друк; рідкокристалічний еластомер; моделювання методом скінченних елементів; схема Морі-Танаки; функція розподілу; функція форми